Development of Competency-Based Approach to Education - Holubnycha, Liudmyla; Shchokina, Tetiana; Soroka, Natalia; Besarab, Tetiana (Educational Challenges, 2022)
The paper deals with competency-based education. Both the development of the category “competence” and application of competences in educational sphere were considered. The purpose is to examine the development of competency-based approach to teaching and learning from the standpoint of modern educational paradigm. The methods of the investigation are analysis and syntheses of the associated researches used to collect and present the findings and draw the conclusion. The results revealed that competency-based education appeared under the influence of the term “competence”; in its development three main stages may be distinguished: 1) 1960-1970 (introduction of the category “competence” in the theory and practice of language learning); 2) 1970-1990 (extension of the studied phenomenon to the field of management and leadership); 3) since the 1990s to the present (comprehensive consideration and analysis of the stated category; finding the blocks of competencies, the principles of systematization; studying the structure of competencies). The conclusion is that in modern educational system competency-based approach is one of the central as existence of the system of competences contributes in description of academic and professional profiles, levels and results of higher education at the international level. Moreover, due to the application of the system of competencies, the process of expanding academic and professional recognition and mobility, as well as increasing the comparability and compatibility of diplomas and qualifications has become possible.